#TITLE_ALTERNATIVE# - MAGDALENA (NIM 10107072); Pembimbing : Prof. Dr. Sutawanir Darwis, FERAWATI
Porosity is a parameter reservoir capable of absorbing and storing oil reserves. If the value of the greater porosity of a reservoir, then the reservoir capacity to absorb the oil will be even greater, so that saved a lot of oil reserves. Optimizing of a reservoir can done with estimating the parameters of porosity. The method used to estimate porosity with how to update the value of porosity in a sequential manner is called Ensemble Kalman Filter (EnKF). EnKF is a method to perform history matching, it is the process of alignment between the model simulation with actual reservoir conditions. In this final project, models of one well reservoir will be developed into models of two wells reservoir with the assumption that there is no interaction between the wells and resevoir boundary condition : constant rate production, infinite acting, line source. EnKF method used to estimate the parameters of porosity in the reservoir one well, using empirical data and simulation data in the initialization state, and two reservoir wells with simulation data.